Conflict of interest in the professions - Davis, Michael, 1943-; Stark, Andrew, 1956- (Practical and professional ethics series., 2001)
The notion of conflict of interest is more relevant today than ever. Ethical sensitivities about the relationship between professionals and those they serve is a source of constant debate. This book sets a new standard for work on this perennial topic, collecting a set of practical essays bytop applied ethicists on a wide variety of professions and occupations. Some conflicts of interest arise because a profession takes on many roles while serving one goal; others take on one role but serve multiple goals. Some conflicts are internal to the profession; others (such as family or business.